1986
DOI: 10.1128/iai.53.3.671-677.1986
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of microorganisms isolated from periodontal lesions in the pathogenesis of inflammatory bowel disease

Abstract: A total of 20 patients with inflammatory bowel disease (IBD) (Crohn's disease, ulcerative colitis) were evaluated with regard to the role of infectious agents and host response. Patients were selected based upon oral manifestations of their disease, 10 with periodontal disease and 10 without. Microbiologic studies of the periodontal flora of IBD-affected patients revealed a unique microflora composed predominantly of small, motile, gram-negative rods, which were most consistent with the genus Wolinella. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
5

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 41 publications
3
66
0
5
Order By: Relevance
“…Several studies have demonstrated that oral changes occur in patients with IBD (15)(16)(17)(18)(19)(20)(21)(22). Inflammatory bowel disease has also been associated with persistent oral lesions in pediatric populations (23).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that oral changes occur in patients with IBD (15)(16)(17)(18)(19)(20)(21)(22). Inflammatory bowel disease has also been associated with persistent oral lesions in pediatric populations (23).…”
Section: Methodsmentioning
confidence: 99%
“…Further support for the concept that reduced neutrophil numbers or function increase the periodontal susceptibility of patients comes from the studies of diabetics (17, 91), reduced chemotaxis in Down's syndrome (60) and neutrophil dysfunction in people with Papillon-Lefevre syndrome (156). Van Dyke et al (154) found that people with inflammatory bowel disease, including those with Crohn's disease and ulcerative colitis, had defects in neutrophil chemotaxis. They found that people with ulcerative colitis had reduced cell associated chemotaxis as compared with control subjects, whereas in those with Crohn's disease, the neutrophil cell-associated chemotactic response was not significantly different.…”
Section: Systemic Diseases and Periodontal Diseasementioning
confidence: 99%
“…Most reports on the oral features of CD deal with soft-tissue lesions rather than periodontal findings. A possible association between IBD and periodontal disease was assumed, in particular that IBD patients are more susceptible to periodontal destruction than the general population (Lamster et al 1978, van Dyke et al 1986, Engel et al 1988, Flemmig et al 1991, Sigusch 2004.…”
mentioning
confidence: 99%